2016
DOI: 10.1007/s12264-016-0055-4
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokines and Alzheimer’s Disease: A Review from the Perspective of Genetic Polymorphisms

Abstract: Neuroinflammatory processes are a central feature of Alzheimer's disease (AD) in which microglia are over-activated, resulting in the increased production of proinflammatory cytokines. Moreover, deficiencies in the antiinflammatory system may also contribute to neuroinflammation. Recently, advanced methods for the analysis of genetic polymorphisms have further supported the relationship between neuroinflammatory factors and AD risk because a series of polymorphisms in inflammation-related genes have been shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
128
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(137 citation statements)
references
References 140 publications
(166 reference statements)
5
128
0
4
Order By: Relevance
“…It has been reported that PICs are involved in alterations of cellular damage related to development of AD and significant increases in IL-1 β, IL-6 and TNF-α in the brain were observed following αβ 1-42 injection [33]. Consistent with the previous results, our present data further demonstrated that AD induces increasing levels of IL-1β, IL-6 and TNF-α in the hippocampal tissues.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It has been reported that PICs are involved in alterations of cellular damage related to development of AD and significant increases in IL-1 β, IL-6 and TNF-α in the brain were observed following αβ 1-42 injection [33]. Consistent with the previous results, our present data further demonstrated that AD induces increasing levels of IL-1β, IL-6 and TNF-α in the hippocampal tissues.…”
Section: Discussionsupporting
confidence: 92%
“…Whereas inhibition of the enzymatic activity of Caspase-3 likely provides a mechanism to attenuate the cellular apoptosis, our data suggests a beneficial role played by activation of mTOR. Elevated levels of PICs in the hippocampal tissues are associated with increased disease vulnerability and AD-related pathological changes such as cell death [33]. Our data also showed that inhibition of mTOR increases upregulation of IL-6 and TNF-α in AD rats, but not IL-1β.…”
Section: Discussionsupporting
confidence: 61%
“…The expressions of IL-1β, IL-6 and iNOS are associated with neurodegenerative diseases. The IL-1β is a potent neuroimmune mediator that takes effect on various cell types including neurons and microglia [38]; iNOS expression is elevated in activated microglia with its synthetic product nitric oxide being one of the major causes of neurodegenerative diseases [39]; and the expression of IL-6 is also strongly linked to AD as an inflammatory mediator [40, 41]. These results thus provide implications that GLP might exhibit neuroinflammation modulatory effects in neurodegenerative diseases such as AD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a therapeutic approach targeting that 5′-flanking rs2027432 polymorphism is strongly associated with late-onset AD in Chinese population [33]. In a meta-analysis study, Di Bona and coworkers show that the IL1B +3953 TT genotype is associated with increased AD risk, while IL1B -511 TT genotype only increases AD risk in Caucasians [34]. Furthermore, studies demonstrate that mutations in the IL-18 gene are also associated with the development of AD.…”
Section: Nlrp3 Pathway As a Target For Ad Treatmentmentioning
confidence: 99%